Tierras y recursos económicos de las aldeas indígenas de Rio de Janeiro: conflictos y negociaciones (siglos XVII-XIX) - Maria Regina Celestino de Almeida (Nuevo mundo - Mundos Nuevos, 2011)
For centuries Indian villages, which were located quite near or even inside urban centers in the colonial society of Rio de Janeiro, were integrated into their productive activities and used to the practice of negotiation with their territory. This had for effect an increase in land conflicts, in spite of negotiations, as Indians tried to keep control over their land and resources. Based on documents about disputes over Indian lands and work in 18th and 19th centuries, this article intends to analyze these conflicts and negotiations taking into account Indians’ motivation and advantages.